THE ROLES OF OTORITAS JASA KEUANGAN TO OVERCOME FICTIVE INVESTMENT BENGKULU CITY - Herawan Sauni; Dimas Dwi Arso (University Of Bengkulu Law Journal, 2018)
This research is purpose to know the role of Otoritas Jasa Keuangan in overcome fictitious investment in Bengkulu city and To know the efforts of Otoritas Jasa Keuangan to protect the consumers that take fictitious investment in Bengkulu city. This research uses empirical approach, that is research in the place by using interviews to get answers about the role of Otoritas Jasa Keuangan to overcome fictitious investment in Bengkulu city and the efforts of Otoritas Jasa Keuangan to protect consumers that has done fictitious investment in Bengkulu City. This research uses two types of data,that is primary data and secondary data. Then, its data to be analyzed in a research report that is qualitative descriptive. The results of the research is the role of Otoritas Jasa Keuangan to  overcome fictitious investment in Bengkulu City that is preventive and repressive efforts. The preventive efforts for example to socializing and educating people to alert investment and coordinating with law enforcers and other regulators. The repressive efforts, for example set up an Alert Investment task force in every area. Then the efforts of Otoritas Jasa Keuangan to protect consumers that have  fictitious investment in Bengkulu City is regulated in POJK Number 1 / POJK.07 / 2013 about Perlindungan Konsumen Sektor Jasa Keuangan